Practices and risks in wild meat consumption: Insights from communities along the Kenya-Tanzania border - Patel, Ekta; Martin, A.; Funk, S.M.; Yongo, M.; Compton, J.; Lauridsen, M.; Fa, J.E. (International Livestock Research Institute, 2024)
Understanding the complex interplay between cultural practices and potential disease risks from wild meat consumption is critical for developing effective One Health and biodiversity conservation strategies. This knowledge brief sheds light on how communities at the Kenya-Tanzania borderlands perceive and manage these risks post COVID-19 as well as assessing the impact of the pandemic on wildmeat consumption, providing valuable insights for policymakers and local leaders aiming to balance human and animal health, biodiversity conservation, and local livelihoods in a region where these factors are intricately linked.